Autophagy Protects Against Developing Increased Lung Permeability and Hypoxemia by Down Regulating Inflammasome Activity and IL-1β in LPS Plus Mechanical Ventilation-Induced Acute Lung Injury - Nosaka, Nobuyuki; Martinon, Daisy; Moreira, Debbie; Crother, Timothy R.; Arditi, Moshe; Shimada, Kenichi (Frontiers in Immunology, 2020)
Targeting inflammasome activation to modulate interleukin (IL)-1β is a promising treatment strategy against acute respiratory distress syndrome. Autophagy is a key regulator of inflammasome activation in macrophages. Here, we investigated the role of autophagy in the development of acute lung injury (ALI) induced by lipopolysaccharide (LPS) and high-volume mechanical ventilation (MV). Mice with myeloid-specific deletion of the autophagic protein ATG16L1 suffered severe hypoxemia and increased lung permeability with significantly higher IL-1β release into alveolar space. Induction of autophagy by fasting-induced starvation led to improved arterial oxygenation and lung permeability, followed by significantly suppressed IL-1β production. Intratracheal treatment with anti-IL-1β monoclonal antibody (mAb) significantly improved arterial oxygenation as well as lung permeability. On the other hand, deletion of IL-1α gene or use of anti-IL-1α mAb provided no significant protection, suggesting that the LPS and MV-induced ALI is primarily dependent on IL-1β, but independent of IL-1α. These observations suggest that autophagy has a protective role in controlling inflammasome activation and production of IL-1β, which plays a critical role in developing hypoxemia and increased lung permeability in LPS plus MV-induced acute lung injury.